Successful IS/IT projects in healthcare: Pretesting a questionnaire - Gomes, J. (2021)
Over the last decade, health systems have faced growing challenges, due mainly to population-ageing and an increase of chronic diseases, which lead to a significant rise in costs and difficulties in accessing healthcare. Countries have made a huge effort that has mainly consisted in significant increase in health financing the expansion of health services facilities, the adoption of new information systems and technology (IS/IT), improving access to medicines, and continued endeavours to enhance organizational management and the sustainability of healthcare services. IS/IT will undoubtedly represent an important tool for providing adequate answers to all these challenges and these systems have the potential to reduce healthcare costs, as well as to improve outcomes. The recognition of project management and maturity models has been evidenced over the last years by the large investments made by health organizations to develop competencies and skills. This paper proposes a new approach, which assumes that project management will mediate the relationship between organisational maturity and the success of IS/IT projects. The questionnaire developed for this research was pre-tested. The advantages of this procedure are discussed in detail. The results allowed for a more reliable definition of the three scales that support the analytical model.